2012
DOI: 10.1002/eji.201242679
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Fas ligand expression is required to induce T‐cell apoptosis and recovery from experimental autoimmune encephalomyelitis

Abstract: In T-cell-mediated autoimmune diseases of the CNS, apoptosis of FasKeywords: Autoimmunity r Astrocytes r EAE r FasL Additional supporting information may be found in the online version of this article at the publisher's web-site Introduction EAE is a widely used animal model to study MS, an inflammatory demyelinating disease mediated by accumulation of T lymphocytes and macrophages in the CNS [1,2]. EAE can be induced by either active immunization with myelin Ags including myelin oligodendrocyte glycoprotein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 46 publications
(62 reference statements)
0
36
0
Order By: Relevance
“…On the other hand, the detection of FasL transcripts in the present study could be explained by activation-induced cell death of activated T cells in the brain [54]. In experimental autoimmune encephalitis, astrocytes expressing FasL have been implicated in T cell homeostasis [55]. …”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, the detection of FasL transcripts in the present study could be explained by activation-induced cell death of activated T cells in the brain [54]. In experimental autoimmune encephalitis, astrocytes expressing FasL have been implicated in T cell homeostasis [55]. …”
Section: Discussionmentioning
confidence: 87%
“…FasL is highly expressed in reactive astrocytes in ischemia, brain trauma, Alzheimer’s disease, encephalomyelitis and multiple sclerosis (Choi and Benveniste, 2004). Astrocytes are the main source of FasL against invading T cells in encephalomyelitis (Wang et al, 2013). Plasmin cleaves FasL at Arg144, releasing sFasL as a diffusible cell death signal (Bajou et al, 2008; Fang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that TNF-treated astrocytes up-regulates Galectin-9 to promote encephalitogenic T-cell apoptosis (Steelman et al, 2013). Xu Wang et al (Wang et al, 2013) used GFAP-Cre FasL fl/fl mice in EAE model and concluded that astrocytes induced apoptosis of Fas + activated CD4 + T cells and to increase numbers of Foxp3 + Treg cells beyond the time point of maximal clinical disease. The FasL expression on astrocytes and its role in induction of T cell apoptosis have also been documented in other literatures.…”
Section: Interaction Between Astrocytes and T Cells Under Pathologmentioning
confidence: 99%